Organic bench model applied to surgical suture training (Research, Society and Development, 2020)
Veterinary and human medicine students should be trained in skills necessary to perform surgical procedures. Regarding the practice of surgical sutures, the methods used include the use of various materials such as fabric device, sponge, pieces of the animals and pieces of ethylene vinyl acetate. This article proposes to use banana and eggplant to train surgical suture techniques. The work was carried out by monitors from the veterinary surgical technical discipline. These monitors performed sutures in the vegetables (green banana and eggplant) and completed a questionnaire on the method. All monitors agreed that vegetables are easy to handle. Most stated that it was a pleasant experience for not using live animals. An advantage of using vegetables is handling, including storage and disposal. Besides, they do not transmit diseases. Animal materials such as bovine tongue, and swine parts that are widely used in suture teaching, present the risk of zoonosis transmission. The proposed organic bench model (banana and eggplant) may be indicated as a complementary alternative to advanced surgical sutures training. In addition, the model in question avoids the use of animals, while respecting ethical and legal issues.